The Five Minute Rule, Ten Years Later - Gray, Jim; Graefe, Goetz (1997)
Simple economic and performance arguments sug-gest appropriate lifetimes for main memory pages and suggest optimal page sizes. The fundamental tradeoffs are the prices and bandwidths of RAMs and disks. The analysis indicates that with today's tech-nology, five minutes is a good lifetime for randomly accessed pages, one minute is a good lifetime for two-pass sequentially accessed pages, and 16 KB is a good size for index pages. These rules-of-thumb change in predictable ways as technology ratios change. They also motivate the importance of the new Kaps, Maps, Scans, and /Kaps, /Maps, /TBscan metrics.